2019
DOI: 10.1101/542282
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-allelic APRR2 Gene is Associated with Fruit Pigment Accumulation in Melon and Watermelon

Abstract: 23Color and pigment content are important aspects of fruit quality and consumer 24 acceptance of cucurbit crops. Here, we describe the independent mapping and cloning 25 of a common causative APRR2 gene regulating pigment accumulation in melon and 26 watermelon. We initially show that the APRR2 transcription factor is causative for the 27 qualitative difference between dark and light green rind in both crops. Further analyses 28 establish the link between sequence or expression level variations in the CmAPRR2 … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(42 citation statements)
references
References 44 publications
1
41
0
Order By: Relevance
“…To further explore the origin and evolution of flower color in O. fragrans , we identified significant QTLs and genomic regions associated with red/orange color through a GWAS in which several genes, such as PMVK, ERF2, and APRR2, were characterized. Among them, APRR2 has been reported to support carotenoid biofortification; it also increases the plastid number and area as well as pigment content, enhancing the levels of chlorophyll in immature unripe fruits and carotenoids in red ripe fruits when it is overexpressed 71 , 72 . ERF6 was reported to bind to the CCD4 promoter and stimulate CCD4 expression, thereby regulating the synthesis of β-ionone in O. fragrans petals 9 .…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the origin and evolution of flower color in O. fragrans , we identified significant QTLs and genomic regions associated with red/orange color through a GWAS in which several genes, such as PMVK, ERF2, and APRR2, were characterized. Among them, APRR2 has been reported to support carotenoid biofortification; it also increases the plastid number and area as well as pigment content, enhancing the levels of chlorophyll in immature unripe fruits and carotenoids in red ripe fruits when it is overexpressed 71 , 72 . ERF6 was reported to bind to the CCD4 promoter and stimulate CCD4 expression, thereby regulating the synthesis of β-ionone in O. fragrans petals 9 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of MYB-type transcription factors participate in plant pigment development and rind coloration in cucumber, sweet cherry, tomato, apple, and rice [35,36] that the APRR2 gene is associated with fruit pigment accumulation in both melon and watermelon, and the gene CICG09G012330 in watermelon was selected as the candidate gene for the light green phenotype. Alternative splicing was speculated to be responsible for a 16-bp deletion in the mRNA of the light rind parent [13]. In the present study, the transcriptional level in the light green material WT2 was also considerably different from that in the dark green material WM102 (Fig.…”
Section: Discussionmentioning
confidence: 45%
“…Weetman proposed the hypothesis that there existing two genes responsible for the foreground stripe pattern and background color, respectively [12]. With help of GWAS analysis, Oren found that a 16-bp deletion in gene CICG09G012330 is the key factor for the light/dark green appearance [13]. With two constructed families, Kumar found that the solid dark green appearance follows a duplicate dominant epistasis fashion [14].…”
Section: Introductionmentioning
confidence: 99%
“…The final SNP set consisted of 4M SNPs. The whole-genome sequence alignment and derived HapMap from the 25 founders are now useful tools for detection of potential causative polymorphisms within candidate genes (Oren et al , 2019)…”
Section: Methodsmentioning
confidence: 99%